Effectivenessof the Anammox Process for Nitrogen Waste Treatment in Tropical Environments: A Comprehensive Review - Frentina Murti Sujadi; Jefri Anjaini; Baruna Kusuma; Asro Nurhabib; Lilik Setiyaningsih; Setyo Budi Kurniawan (Jurnal Biologi Tropis, 2025)
The anaerobic ammonium oxidation (Anammox) process is a biological mechanism that converts ammonium and nitrite into nitrogen gas without the need for oxygen, making it a potentially efficient solution for nitrogen waste treatment. This study aims to analyze the effectiveness of Anammox in reducing nitrogen concentrations from various types of waste and compare it with conventional methods. This study was conducted using a systematic literature review approach on the effectiveness of the Anammox process in nitrogen removal from wastewater. The analysis was carried out by extracting information related to reactor types, operational parameters (pH, temperature, C/N ratio, and substrate concentration), nitrogen removal efficiency, and inhibitory factors. The results show that this process can consistently reduce ammonium and nitrite, with performance highly influenced by operational conditions. Factors such as microbial stability, temperature, and nitrite availability are the main determinants of success. This study confirms that Anammox offers a more energy-efficient approach, producing less sludge and being more environmentally friendly compared to nitrification–denitrification. Thus, Anammox technology contributes to the development of sustainable wastewater treatment systems while expanding scientific understanding of the role of Anammox bacteria in the nitrogen cycle.